Entrepreneurial Framework Conditions and Business Sustainability among the Youth and Women Entrepreneurs - Orobia, Laura A.; Tusiime, Immaculate; Mwesigwa, Rogers; Ssekiziyivu, Bob (Asia Pacific Journal of Innovation and Entrepreneurship, 2020)
This study aims to investigate the relationship between entrepreneurial framework conditions (EFCs) and business sustainability among youth and women entrepreneurs using the institutional theory. This study is cross-sectional and follows an explanatory research design using 390 youth and women entrepreneurs in Mbarara district (Uganda). A principal factor analysis was conducted to single out the particular constructs of business sustainability and EFC. Inferential analysis was conducted to test the relationships. First, the constructs of business sustainability are stakeholder engagements, people and skills, ecosystem management, market and sales and innovation. Second, the constructs of EFC are education, government program and policies, IT infrastructure, market openness and finance. Finally, finance and IT infrastructure are significant predictors of business sustainability among the youth and women entrepreneurs.
Keywords: Youth, Business sustainability, Women, Entrepreneurial framework condition